Cochlear Implantation in Charcot-Marie-Tooth Disease: Case Report and Review of the Literature - C. Lane Anzalone; Sarah Nuhanovic; Amy P. Olund; Matthew L. Carlson (Case Reports in Medicine)
Introduction. Charcot-Marie-Tooth (CMT) disease is a peripheral hereditary neuropathy associated with motor and sensory impairment and can result in profound sensorineural hearing loss (SNHL). Currently, the role of cochlear implantation in the setting of CMT and other progressive peripheral neurodegenerative disorders is not well established. Methods. Case report and review of the English literature. Results. A 70-year-old male with CMT was referred for evaluation of progressive asymmetric SNHL and reported a 15-year duration of deafness involving the left ear. Audiometric testing confirmed profound SNHL in the left ear, while the right ear exhibited moderate-to-severe SNHL. Left-sided cochlear implantation was performed using a conventional length lateral wall electrode. Intraoperative device testing found normal impedance levels throughout the array; however, electrically evoked auditory potentials were absent on all electrodes. Upon initial activation 3 weeks after surgery, the patient reported excellent access to sound in the cochlear implant-only condition. He has made good progress at each subsequent visit; speech perception testing after seven months showed improvement from 0% to 32% on AzBio sentence and 53% on CNC phoneme testing in the cochlear implant-only condition. Conclusion. We report the third case of cochlear implantation in a patient with CMT. SNHL in CMT is hypothesized to result from disruption of synchronous activity of the cochlear nerve. In patients with CMT, cochlear implantation may reconstitute synchronous neural activity by way of supraphysiological electrical stimulation. Our results corroborate two earlier reports that cochlear implantation is a viable option for rehabilitation of SNHL in this unique subset of patients.